Impacts of marine heat extremes on bivalves - Masanja, Fortunatus; Yang, Ke; Xu, Yang; He, Guixiang; Liu, Xiaolong; Xu, Xin; Xiaoyan, Jiang; Xin, Luo; Mkuye, Robert; Deng, Yuewen; Zhao, Liqiang (Frontiers in Marine Science, 2023)
As the global ocean continues to experience the consequences of an increase in the frequency and intensity of heat waves, the trend is expected to persist into the 21st century, with a projected tripling of heat waves by 2040. This phenomenon poses a significant threat to marine ecosystems and the survival of marine organisms, including the ecologically and economically vital bivalves. Bivalves are vulnerable to harm from heat stress at various levels of biological organization, and their growth can be negatively impacted by high temperatures, potentially leading to mass mortalities and posing a threat to ecosystem quality and food security. In light of these concerns, this review aims to provide a comprehensive examination of the effects of heat stress on bivalves. It summarizes the physiological and biochemical changes that bivalves undergo in response to extreme heat events and offers an overview of the strategies they employ to mitigate their impacts. A better understanding of the underlying mechanisms of bivalve responses to heat stress is crucial in order to fully appreciate the impact of these events on these organisms. This review synthesizes the current knowledge on heat stress in bivalves and highlights the importance of further research in this area. By providing a comprehensive overview of the physiological and biochemical changes that bivalves experience during heat stress and the strategies they use to mitigate its impact, this review aims to support the development of more effective approaches to minimize heat stress in bivalves.